LABORATORY DIAGNOSIS OF COVID-19 IN THE KYRGYZ REPUBLIC (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The purpose of this project was to analyze the features of the circulation of theSARS-CoV-2 coronavirus infection in the territory of the Kyrgyz Republic.The growth dynamicsof laboratory research depends on the increase in the incidence and genetic lines of the new SARSCoV-2 coronavirus. For the period from 2020 to 2022, a laboratory investigation of 2,552,212samples of COVID-19 was carried out using the RT-PCR method.For SARS-CoV-2 genomic monitoring, positive RT-PCR samples were sent for confirmation and genetic sequencing.
Keywords: coronavirus infection, SARS-CoV-2, RT-PCR